The impact of COVID-19 on breastfeeding rates: An international cross-sectional study - Ganho-Ávila, Ana; Guiomar, Raquel; Sobral, Mónica; Pacheco, Francisca; Caparros-Gonzalez, Rafael A; Díaz-Louzao, Carla; Motrico, Emma; Domínguez-Salas, Sara; Mesquita, Ana; Costa, Raquel; Vousoura, Eleni; Hadjigeorgiou, Eleni; et al. (My University, 2023)
Breastfeeding promotes children's health and is associated with positive effects to maternal physical and mental health. Uncertainties regarding SARS-CoV-2 transmission led to worries experienced by women and health professionals which impacted breastfeeding plans. We aimed to investigate the impact of self-reported and country-specific factors on breastfeeding rates during the COVID-19 pandemic.
Keywords: Breastfeeding; COVID-19; Cross-countries; Perinatal health; SARS-CoV-2